PUBLIC PROCUREMENT IN POLAND: EXPERIENCE FOR UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article analysed the features of public procurement in Poland and the opportunities to apply this experience in Ukraine in order to increase the financial efficiency of these procurement. In particular the Polish Public Procurement Agency executes both a monitoring the formal compliance with the law in procurement procedures and the macro-monitoring of the functioning of the entire public procurement system in Poland, to which Ukrainian Government should pay particular attention. First of all, it concerns the importance of certain indicators of procurement efficiency, which are not always measured by cost savings (and the methods of calculating cost savings are a rather debatable issue).The purpose of the article is to reveal the main features of public procurement in Poland.The Supreme Chamber of Control of Poland and its regional units control public procurement mainly after the conclusion of the contract; while not limiting the ability of the Chamber of Control to verify procurement during their implementation too; public procurement audits can be carried out at any stage of procurement, which is also important to consider in Ukraine.The structure of the Office of the Public Procurement Agency of Poland, which employs only 130 people, is also effective. The structure includes 7 departments, in particular, the law department, 2 control departments, education and analysis information department, appeal department, organizational and financial department, internal audit department. Control departments are divided into two areas depending on using of funds – funds from the state budget (21 people) and EU funds (21 people). Verification of compliance with procurement law by customers is the responsibility of the control departments. At the same time there are more than 3,000 people in the State Audit Service of Ukraine, including regional divisions. The issue of financial responsibility in Poland is governed by a special Law on Violation of Budget Discipline. In particular, this Law provides for the following types of financial punishment: warning; reprimand; a fine; prohibition to perform the functions as an official. If a punishment is determined as a reprimand, the person is not entitled to receive bonuses, other incentive payments during the term of punishment. If only a warning is imposed then the premium can be paid.
Keywords: public procurement, European Union, Poland, Ukraine